A Non‐coded β2, 2‐Amino Acid with Isoxazoline Core Able to Stabilize Peptides Folding through an Unprecedented Hydrogen Bond. Issue 39 (28th July 2022) - Bucci, Raffaella; Vaghi, Francesco; Di Lorenzo, Davide; Anastasi, Francesco; Broggini, Gianluigi; Lo Presti, Leonardo; Contini, Alessandro; Gelmi, Maria Luisa
Abstract : New peptidomimetics containing a β 2, 2 ‐isoxazoline amino acid, 5‐(aminomethyl)‐3‐phenyl‐4, 5‐dihydroisoxazole‐5‐carboxylic acid (Isox‐β 2, 2 AA), were prepared and studied by NMR and theoretical calculations. Interestingly, inserting R ‐Isox‐β 2, 2 AA in short tri‐ and hexapeptide models, an unexpected α‐turn‐like motif was observed, thanks to an unprecedented strong H‐bond involving C=N of isoxazoline side chain of β 2, 2 AA.